Transformasi Identitas Sosial Komunitas Punk Sorak dalam Kontribusinya terhadap Gerakan Lingkungan Berkelanjutan - Mustakim, Zaenal (Epistemik: Indonesian Journal of Social and Political Science, 2025)
The punk subculture has long provided a platform for marginalized groups to express identity and resist social, political, and environmental injustices. Nevertheless, punk communities are often burdened with negative stereotypes portraying them as deviant. This study examines the role of the Punk SORAK (Soeara Rakjat) community in Pekanbaru in promoting public awareness of environmental sustainability movements. Utilizing a qualitative approach and phenomenological methods, the research explores the dynamics of Punk SORAK’s collective identity and its efforts to counter social stigma through environmental initiatives, including climate change campaigns, collaborations with environmental organizations, and community-based activities. The findings reveal that Punk SORAK functions not only as a form of resistance to social injustices but also significantly contributes to environmental conservation efforts. The study concludes that public recognition of Punk SORAK can be achieved through gradual social transformation involving intersubjective dialogue, mutual recognition, and solidarity, offering an alternative model for integrating subcultural movements into Indonesia’s broader social and environmental change agendas.